PARENTS’ KNOWLEDGE AND ATTITUDE TOWARD CHICKENPOX AND ITS PREVENTION - Tariq, Islam; Ramzi, Farah; Kasim, Hala F.; Yousif, Salah; Rashid, Suhir M.; Al-Obaidy, Luma M. (Eastern Ukrainian Medical Journal, 2026)
Introduction: Chickenpox is a highly contagious condition, often leading to severe illness in adults and immunocompromised conditions, attributed to the varicella-zoster virus. Therefore, these facts describe the importance and severity of chickenpox that makes prioritizing protection through vaccination a point of need. However, confirmation and utilization depend on the knowledge and attitude of parents. This study was done to assess the knowledge and attitude of parents toward chickenpox and vaccination for its prevention. Methods: This cross-sectional study enrolled 261 parents of children visiting the primary healthcare centres. It used a pretested questionnaire requesting information regarding demographic characteristics along with an assessment of knowledge and attitudes toward chickenpox and the chickenpox vaccine. Appropriate statistics in the descriptive form and in proper tests, including chi-square and Fisher exact tests, were drawn for proper data analysis. Results: 64.4% of the participants were willing to accept chickenpox vaccination for their children. Predictors of willingness to vaccinate were: living in a family with fewer rooms (p=0.028) and being married (p=0.026). In all, 98.2% of those willing to be vaccinated were knowledgeable about chickenpox, compared to 86.0% of those unwilling (p<0.001). There was also a significant correlation between perceived risk of reinfection and attitude towards vaccination (p=0.002). This is an indicative study that shows that educational intervention for parents is necessary to clear myths and misconceptions associated with chickenpox and its prevention. Conclusion: Increasing parents’ knowledge regarding vaccine safety and efficacy and measures taken to ensure the safety of the vaccine and promoting it in the community can help in the acceptance of the vaccine and may further reduce the incidence of chickenpox.